Critical Period Plasticity as a Framework for Psychedelic-Assisted Psychotherapy - Lepow, Lauren; Morishita, Hirofumi; Yehuda, Rachel (Frontiers in Neuroscience, 2021)
As psychedelic compounds gain traction in psychiatry, there is a need to consider the active mechanism to explain the effect observed in randomized clinical trials. Traditionally, biological psychiatry has asked how compounds affect the causal pathways of illness to reduce symptoms and therefore focus on analysis of the pharmacologic properties. In psychedelic-assisted psychotherapy (PAP), there is debate about whether ingestion of the psychedelic alone is thought to be responsible for the clinical outcome. A question arises how the medication and psychotherapeutic intervention together might lead to neurobiological changes that underlie recovery from illness such as post-traumatic stress disorder (PTSD). This paper offers a framework for investigating the neurobiological basis of PAP by extrapolating from models used to explain how a pharmacologic intervention might create an optimal brain state during which environmental input has enduring effects. Specifically, there are developmental “critical” periods (CP) with exquisite sensitivity to environmental input; the biological characteristics are largely unknown. We discuss a hypothesis that psychedelics may remove the brakes on adult neuroplasticity, inducing a state similar to that of neurodevelopment. In the visual system, progress has been made identifying the biological conditions which distinguishes the CP and manipulating the active ingredients with the idea that we might pharmacologically reopen a critical period in adulthood. We highlight ocular dominance plasticity (ODP) in the visual system as a model for characterizing CP in limbic systems relevant to psychiatry. A CP framework may help to integrate the biological influence of the environment both in development and in PAP.